Face recognition and machine learning at the edge - Ling, Joanne Sin Yee, 1993-, author; Usman Ullah Sheikh, 1981-, supervisor; Fakulti Kejuruteraan. Sekolah Kejuruteraan Elektrik (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Sarjana Falsafah) Universiti Teknologi Malaysia, 2019